The Turkish Model: new dynamics on Mediterranean’s policy - Rodrigues, Jorge (Africana Studia, 2020)
The overall changes on the strategic environment has put Ankara on the gravity center of some of the most important international conflicts. With AKP’s recent external policy, breaking away with Atatürk’s legacy of non-interventionism, Turkey opened the way for a new regional strategic chapter. Considering its interests and its influence - which spreads from Afghanistan to Northern Africa, Ankara’s Foreign Affairs Ministry, Davutoglu, developed an important net, independent of the country’s internal situation. This article intends to identify the evolution of this new Turkish foreign policy, and the real influence that Ankara has on this “Southern Corridor”. This requires an affirmative foreign policy, an international actor. Keywords: Turkey, model, corridor, Mediterranean, dilemma.